Limites e potencialidades da relação entre poder público municipal e cooperativas de catadores(as) de materiais recicláveis - Alves, Murilo Mendes (Universidade Federal de São Carlos, 2022)
Recyclable-waste collectors cooperatives are organized and established in various regions of the country as an alternative to the misfortunes brought by unemployment and precarious work, which lead part of the population to seek different forms of subsistence in the economy. The main objective of this research is to identify favorable or unfavorable aspects in relation to the support of the municipal government with the cooperatives of solid waste pickers, which perform the selective collection service in four cities of the State of São Paulo. Thus, the research problem involves the lack of support offered to recycling cooperatives by the municipal government, and it is related to the absence of municipal public policies capable of promoting the socio-productive inclusion of waste pickers and maintain or consolidate existing experiences, a problem that causes negative effects on workers, such as: weakening of the cooperative; precariousness at work and discontinuity of the selective collection service. In order to achieve the proposed objectives, a qualitative descriptive approach was used and the study was carried out in four cities in the interior of the state of São Paulo that are part of the same geographic region and have solidarity economy cooperatives formed in the early 2000s . An extensive bibliographic review was carried out and the information was collected through documents, official websites and complemented by a questionnaire with closed questions directed to municipal public managers and to representatives of the cooperatives. Among the results, regarding the relationship between public authorities and recyclable-waste collectors cooperatives, factors that can promote the strengthening or weakening of collectors cooperatives were evidenced. Municipal legislations were identified with the potential to offer better conditions and overcome the scenario of exploitation and precariousness of the work of collectors, but which are not fully implemented. It was concluded that the hiring of recyclable-waste collectors cooperatives is a fundamental factor to strengthen their activities, but it is also necessary that the public power is properly structured to offer support to the collectors, aiming at the inclusion of more people in the recycling production chain, so that it is also possible to promote the principles of solidarity economy with these workers. Support from the government brings greater security for cooperatives to develop their work and can contribute to greater longevity and sustainability of these enterprises. In this sense, the results of the work indicate that with the support of the public power through the formal contracting of cooperatives and the implementation of government actions that generate effective benefits to the work of the collectors, the cooperatives are able to provide their services appropriately, as well as effecting the inclusion of more workers in the recycling production chain, generating benefits in the economic, environmental and social dimensions.
Limits and potentialities of the relationship between municipal government and cooperatives of recyclable-waste collectors
Keywords: Poder público municipal; Cooperativas de catadores; Políticas públicas; Recyclable-waste collectors cooperatives; Public power; Public policies; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO